Small intestinal mucosal injury and its risk factors in patients with gastrointestinal cancer who developed complicated fluoropyrimidine-induced diarrhea - Miho Sakumura; Takayuki Ando; Ayumu Hosokawa; Takahiko Nakajima; Iori Motoo; Hiroshi Mihara; Akira Ueda; Shinya Kajiura; Sohachi Nanjo; Haruka Fujinami; Kohei Ogawa; Ichiro Yasuda (BMC Gastroenterology, 2020)
Abstract Background Diarrhea is a common adverse event of fluoropyrimidine-based chemotherapy. However, limited data are available on the frequency and risk factors of complicated chemotherapy-induced diarrhea (CID) and small intestinal mucosal damage. In this current study, we aimed to determine the incidence of complicated CID and mucosal injury among patients with complicated CID receiving fluoropyrimidine via small bowel capsule endoscopy (CE) and determined baseline risk factors associated with complicated CID. Methods In total, 536 patients with advanced or recurrent gastrointestinal cancer who received fluoropyrimidine-based chemotherapy were retrospectively analyzed. Diarrhea was evaluated using the Common Terminology Criteria for Adverse Events version 4. Complicated CID was defined according to the American Society of Clinical Oncology guidelines. To evaluate small intestinal mucosal injury in patients with complicated CID, CE was performed. Multivariate analysis was performed to identify risk factors for complicated CID. Results Total number of 32 (6%) patients developed complicated CID. Complicating symptoms were noted in 25 (78%) patients, with cramping, vomiting, and sepsis being observed in 15 (60%), 8 (32%), and 3 (12%) patients, respectively. Among the 13 patients who underwent CE, 11 (85%) showed abnormal findings. Multivariate analysis revealed that oral fluoropyrimidine administration was a risk factor for complicated CID (odds ratio 2.95; 95% confidence interval 1.06–8.19). Conclusions Despite the relatively low incidence of complicated CID, mucosal injury of small intestine was common in patients with complicated fluoropyrimidine-induced diarrhea and oral fluoropyrimidine was an independent risk factor.